The copper-containing proteins and their effect on metabolism - Konkabaeva, A.E.; Arystanbai, A.A.; Mukhanova, Sh.A.; Kolossov, R.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the paper review of the literature on the role of copper in the body is presented. The main content of the study is the analysis of the participation of copper in protein, carbohydrate and fat metabolism. Based on the analysis of literature sources it is shown that copper is a part of many vital proteins and enzymes that influence the development of tissues and cells of the body. The article contains the elucidation of the features of the participation of protein-transporters in the transport of copper through the plasma membrane into intracellular organelles and from the cytosol into the bloodstream. The participation of copper in the metabolism depends on its physic-chemical properties. In the literature review the features of proteins that control copper hemodynamics and participate in copper-dependent signaling are clarified. The characteristic features of copper included in the composition of many enzymes are distinguished and described. It is shown that copper plays an important role in ensuring normal growth and maintaining health. It is indicated that both deficiency and excess of copper in the body lead to various diseases. The conclusion is that the biological effect of copper shows through communication with proteins, forming complexes with high biological activity.
Құрамында мысы бар ақуыздар жəне олардың метаболизмге əсері
Медьсодержащие белки и их влияние на метаболизм
Keywords: copper; metabolism; ceruloplasmin; copper-containing enzymes; deficiency and excess of copper